La Sainte famille sexualité, filiation et parentalité dans l'Église catholique - Peperstraete, Sylvie (Problèmes d'histoire des religions, 2017)
Adopting a diachronic and interdisciplinary approach, this book questions the relationship maintained by the Church and the Catholic world with the family.